Motor activities and sensory education in a natural environment: Knowing the past to know how to plan the future - Ario Federici (Pensa MultiMedia, 2023)
The exploration of the environment through the body and motor skills, become fundamental objectives for the discovery of both physical and geometric space, for the correct structuring of its body scheme by recovering the roots of our being in the world, discovering their memories, objects, The matter of things, of the natural elements of the landscape through action. Exercise in its components integrates perfectly at an interdisciplinary level by promoting recreational-recreational, relational, emotional actions, capable of soliciting a correct relationship with the natural environment. The scouting pedagogy is analyzed to understand the pedagogical methods of directing the boy's evolutionary personality towards the Inter sensorial unit and the most authentic meaning of these activities in a natural environment. Reality is considered as an emotional experience that implies the possibility of an involvement of all senses, modulated according to their magical polyphony.